Eli Mandel's Family Architecture: Building a House of Words on the Prairies - Ravvin, Norman (Canadian Jewish Studies / Études juives canadiennes, 1994)
The latter half of Eli Mandel's career took him to Toronto andabroad, but his writing in these years moved ever back to hischildhood home in Estevan and his connection, through hisgrandfather who was a rabbi and a shochet, to the Jewish pioneeringcolony at Hirsch, Saskatchewan. In his collection, Out of Place,Mandel offers an oblique and haunting account of the effect onhim as a writer, as well as on the Canadian landscape itself, of thenow vanished Jewish colonies at Hirsch and Hoffer. He makes, aswell, an explicit connection between his struggle to address thefate of Hitler's victims and "the place of the Jewish dead on theprairies." The juxtaposition of these themes helps us address therole of memory and Jewish history in Mandel's work.